Empowering the people of God : Catholic action before and after Vatican II - Bonner, Jeremy; Denny, Christopher D.; Connolly, Mary Beth Fraser (Catholic practice in North America., 2014)
Bolstered by a wave of immigration in the early 20th century, a polyglot American Catholic Church struggled to forge a secure subculture in a society that regarded Catholics with suspicion. In the decades that separated the Roaring Twenties from Vatican II, Catholic Action inspired laypeople to participate in the work of the Church's hierarchy. This study examines how American Catholics at the grassroots experienced the evolving pattern of social and religious activism. It demonstrates the pattern both of historical continuity and transformation within the Catholic Church in America.